PROYECTO CURRICULAR DE ESPECIALIZACIÓN EN EDUCACIÓN MATEMÁTICA - Universidad Pedagógica Nacional, Departamento de Matemáticas (Tecné, Episteme y Didaxis: TED, 1999)
What follows is a description of the Specialization program in Mathematics Education; a postgraduate program directed forward students with a Teacher Degree in Mathematics or Mathematics and Physics, or a Bachelor Degree in Mathematics. The objective of the program is the qualification of the Mathematics teacher’s daily practice. The curriculum is developed during three semesters, each of which centers its attention on the didactics of a particular area of school mathematics. Students can choose three of any of the following areas: Calculus, Algebra, Geometry, Probabiity and Statistics, and the Use of Technology in the teaching of school mathematics.